Causative Factors for Femoral Pin Track Fractures in Navigated Total Knee Arthroplasty - TW Ewe; EK Chee; YS Chooi; WM Ng (Malaysian Orthopaedic Journal, 2010)
This retrospective radiographic analysis of 57 patients (62 knees) examined two possible factors involved in pin tract fractures of the femur due to navigated total knee arthroplasty (TKA): the angle of the tracker pin with respect to the lateral femoral cortex, and the distance between the tracker pin and the lateral joint line. Our findings demonstrate a relationship between postoperative pin tract induced stress fractures (3 patients), with pin tract angles exceeding 15°. Pin placement at a site more than 10cm from the lateral joint line, did not show any significant association with risk of fracture. These findings lead to enhanced understanding of the causative factors underlying pin track femoral fractures in TKAs.